Matching Biomedical Ontologies via a Hybrid Graph Attention Network - Wang, Peng; Hu, Yunyan (Frontiers in Genetics, 2022)
Biomedical ontologies have been used extensively to formally define and organize biomedical terminologies, and these ontologies are typically manually created by biomedical experts. With more and more biomedical ontologies being built independently, matching them to address the problem of heterogeneity and interoperability has become a critical challenge in many biomedical applications. Existing matching methods have mostly focused on capturing features of terminological, structural, and contextual semantics in ontologies. However, these feature engineering-based techniques are not only labor-intensive but also ignore the hidden semantic relations in ontologies. In this paper, we propose an alternative biomedical ontology matching framework BioHAN via hybrid graph attention network, and that consists of three techniques. Firstly, we propose an effective ontology enriching method that refines and enriches the ontologies through axioms and external resources. Subsequently, we employ hyperbolic graph attention layers to encode hierarchical concepts in a unified hyperbolic space. Finally, we aggregate the features of both the direct and distant neighbors with a graph attention network. Experimental results on real-word biomedical ontologies demonstrate that BioHAN is competitive with the state-of-the-art ontology matching methods.